Street talk and Bourdieusian criminology: Bringing narrative to field theory - Sandberg, Sveinung (Criminology & criminal justice, 2017)
The work of Bourdieu has increasingly gained interest in criminology. His theoretical framework is rich and arguably the most sophisticated approach to social inequality and difference in sociology. It has however, been criticized for bias towards the structural aspects of social life, and for leaving little space for the constitutive, and creative role of language. We argue for the inclusion of narrative for understanding street fields. Based on qualitative interviews with 40 incarcerated drug dealers in Norway, we describe the narrative repertoire of the street field, including stories of crime business, violence, drugs and the ‘hard life’. The narrative repertoire is constituted by street capital, but also upholds and produces this form of capital. Street talk is embedded in objective social and economic structures and displayed in the actors’ habitus. Narratives bind the street field together: producing social practices and social structure.